Technology for Pre-sowing Encapsulation of Ears Using Biodegradable Polymer Materials - M. O. Kulpina; T. V. Chaplygina; K. A. Stepanov; N. D. Blinov (Сельскохозяйственные машины и технологии, 2024)
The paper highlights that for enhancing technological processes in grain crop breeding, a method for protecting seed material was proposed, accompanied by the development of a device for sowing seeds with unthreshed ears. This approach improves labor productivity during sowing and ensures varietal purity. However, challenges, such as ear jamming in seeder mechanisms and reduced seed productivity per ear were identified. To address these issues, the use of biodegradable polymeric materials, including polyvinyl alcohol and polylactide, is proposed for encapsulating ears sown with a spikelet seeder. (Research purpose) The paper examines the impact of encapsulating Rima wheat ears with biodegradable materials on the quality of sowing using a spikelet seeder and on seed productivity indicators. (Materials and methods) Sowing quality was evaluated using the coefficient of variation of distances between adjacent ears. Seed productivity was evaluated based on stem growth and development using the laboratory-vegetative method, as well as by analyzing the dynamics of plant biochemical composition with infrared spectroscopy. (Results and discussion) The study found that the average variation coefficient during seeding with a spikelet seeder was 15.5 percent for untreated control samples, 11.3 percent, for ears treated with polyvinyl alcohol, and 9.7 percent for those treated with polylactide. For manual seeding, the variation coefficient of control samples averaged 13.1 percent. By the 19th day, plants grown from ear seeds treated with polyvinyl alcohol exhibited growth indices 7 percent higher than the control samples, while those treated with polylactide showed a 13 percent decrease. Biochemical analysis revealed that plants grown from seeds of ears treated with polyvinyl alcohol showed a 19.3 percent increase in water content, a 42.9 percent increase in fats, a 57.2 percent increase in carbohydrates, and a 21.6 percent decrease in protein content compared to the control samples. For plants grown from seeds of ears treated with polylactide, fat content increased by 44.5 percent and carbohydrates by 60.3 percent, while water content decreased by 59.7percent and proteins by 9.3%, compared to the control samples. (Conclusions) The study demonstrates that encapsulating ears with biodegradable materials such as polyvinyl alcohol and polylactide is a promising solution for enhancing the sowing and yield qualities of seeds in grain crop breeding. This technology reduces the coefficient of variation in adjacent ear spacing during sowing, increases plant height, and improves nutrient content. Among the materials studied, polyvinyl alcohol proved to be the most effective for seed breeding due to its superior properties